JOB SATISFACTION AS A MODERATING VARIABLE BETWEEN THE EFFECT OF COMPENSATION AND LEADERSHIP STYLE ON TURNOVER - Abdi Fadhlan (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The company's goals depend not only on modern equipment, good facilities, and infrastructure but also on the people who carry out this work. A company's success is strongly influenced by human resources, which are the company's driving force. Quality human resources can be seen from how the output is displayed. Therefore, companies must pay attention to the actions and needs of their workers to provide work results that are in line with company expectations. This study aims to see how the effect of compensation and leadership style on turnover is moderated by job satisfaction. This research uses quantitative methods. The sample size for this study was 107 employees of PT. Locco Mandiri Indonesia by collecting data through a questionnaire. SPSS or PASW (Predictive Analytics Software) is used to analyze the data in this report. The findings of this study are: 1) Compensation has a positive and significant effect on turnover intention. 2) Leadership style has a positive and significant effect on turnover intention. 3) Job satisfaction has a positive and significant effect on turnover intention. 4) Compensation has a positive and significant effect on turnover intention, moderated by job satisfaction. 5) Leadership style has a positive and significant effect on turnover intention moderated by job satisfaction.